(untitled) (Globalization and Business, 2023)
Contemporary world admits and analyses the destroying results and consequences of the largest-ever bankruptsy of the Lehman Brothers Investment bank which lead to the mortgage crisis and turned into the global one. The recession continues up to present, i.e. almost for ten years. Leading economists forecast the further negative issues and confess that the economic figures would never go back to the ones we had back ten years ago. The extreme points of consideration the recession and the crisis issues are in contradiction with the economic theory which predicts further recession though may never provide consistent and exact figures and dates. The reflection of the crisis onto the economic theory and science may provide further materials for discussions and arguments against existence of the crisis, as the global economy development never interrupted. Moreover, the world faced the birth of an absolutely new and enigmatic product on the market – cryptocurrency. The question is: would the cryptocurrency bring the relief in terms of recession or would it lead to a new default of the market? The economic science estimates the pros and cons of the existing risks and market threats and hopefully will play its substantial role in eliminating them.